The impact of breathing on HRV measurements: Implications for the longitudinal follow-up of athletes - Saboul, D.; Pialoux, V.; Hautier, C. (European Journal of Sport Science, 2013)
The purpose of the present work was to compare daily variations of heart rate variability (HRV) parameters between controlled breathing (CB) and spontaneous breathing (SB) sessions during a longitudinal follow-up of athletes. HRV measurements were performed daily on 10 healthy male runners for 21 consecutive days. The signals were recorded during two successive randomised 5-minutes sessions. One session was performed in CB and the other in SB. The results showed significant differences between the two respiration methods in the temporal, nonlinear and frequency domains. However, significant correlations were observed between CB and SB (higher than 0.70 for RMSSD and SD1), demonstrating that during a longitudinal follow-up, these markers provide the same HRV variations regardless of breathing pattern. By contrast, independent day-to-day variations were observed with HF and LF/HF frequency markers, indicating no significant relationship between SB and CB data over time. Therefore, we consider that SB and CB may be used for HRV longitudinal follow-ups only for temporal and nonlinear markers. Indeed, the same daily increases and decreases were observed whatever the breathing method employed. Conversely, frequency markers did not provide the same variations between SB and CB and we propose that these indicators are not reliable enough to be used for day-to-day HRV monitoring.